Faktor - Faktor Yang Berhubungan Dengan Kejadian Pneumonia Pada Pasien Di Intensive Care Unit ( Icu ) Rumah Sakit Islam Surakarta - Santoso, Budi; , Irdawati S. Kep., Ns., M.Si., Med; , Sahuri Teguh K., S.Kep., Ns (2015)
Approximately 80% of patients had suffered from respiratory tract infections, pneumonia both communities, and Nosocomial Pneumonia. Which include the type of acute pneumonia, there are around 15-20%. The incidence of Nosocomial Pneumonia in ICU nearly 25% of all cases of infection that exists and 90% occurred in patients on ventilators. Identification of the factors predisposing to pneumonia could be used for prevention and containment procedures the disease.This study aims to determine the factors associated with the incidence of pneumonia in patients admitted in the Intensive Care Unit (ICU) Surakarta Islamic Hospital.This type of research is Quantitative Descriptive Analytical Cross Sectional approach by taking a sample of 50 patients. Data collection instruments used were observation sheet. Statistical analysis using Chi-square correlation techniques.Results of univariate analysis of 50 respondents was noted as many as 18 people (36%) suffered from pneumonia. In the bivariate analysis of the age variable chi-square value of 8,631 respondents (ρ = 0.003), history of 2,585 smokers chi-square value (ρ = 0.108), use of ventilator chi-square value of 9.992 (ρ = 0.002), decreased awareness of the value of chi square 11.314 (ρ = 0.001), surgery chi-square value of 0.547 (ρ = 0.459), and chronic disease chi square 5.246 (ρ = 0.022). Factors - factors associated with pneumonia based on the value of ρ <0.05. It can be concluded that the factors - factors associated with pneumonia in patients admitted to the ICU diruang RS. Surakarta Islamic age, the use of a ventilator, loss of consciousness and chronic diseases.